Fatigue behavior and damage modes of high performance poly-ether-ketone-ketone PEKK bilayered crowns. (October 2020) - Alsadon, Omar; Wood, Duncan; Patrick, David; Pollington, Sarah
Abstract: Objectives: To evaluate and compare the fatigue behavior (fatigue limit and fatigue life) and damage modes of high-performance poly-ether-ketone-ketone (PEKK), zirconia and alloy bilayered crowns. Materials and methods: A total of 110 crowns (n = 50 for fatigue limit and n = 60 for fatigue life) were fabricated and used in this study. Pekkton® ivory discs, yttrium stabilized zirconia blanks and NiCr casting alloy were used to produce the respective PEKK, zirconia and alloy copings for crown fabrication. The prepared crowns were veneered with composite resin and subjected to fatigue tests. The fatigue limit was evaluated using the staircase method and the fatigue life of the samples was evaluated by subjecting the crowns to a load lower than the fatigue limit of that particular group, and also with an intermediate load of 522 N. A graphical plot was generated from the shape parameter (β) and life parameter (α) values obtained through the Weibull analysis method. Kruskal-Wallis and Mann-Whitney tests were applied to determine the significance differences in the recorded fracture mode between the study groups. The damage modes of the samples were assessed using Burke's classification. Results: The recorded fatigue limits of the groups were 442.8 ± 42.1 N, 608.7 ± 7.6 N, and 790.4 ± 29.2 N for zirconia, NiCr and PEKK, respectively. A significant difference in the fatigue limit of the groups was observed ( p  < 0.05). PEKK samples demonstrated the highest survival cycles of 1, 170, 000 and the lowest survival cycles was observed with zirconia samples at 100, 000 under 522 N loading. The fracture modes in PEKK samples were largely distributed between code 1 and 2 whereas the fracture modes in NiCr group was distributed between code 1 and 4 and YZ crowns exhibited more of code 5 fractures. The difference in fracture modes among the groups was statistically significant ( p  < 0.05). Conclusion: The PEKK group demonstrated better results compared to zirconia and NiCr based crowns. The PEKK group demonstrated high fatigue limit and survived the highest fatigue life cycles among the tested groups.